특수학교 고교학점제에서 선택과목 개설 및 운영의 다양화를 위한 지원 방안 탐색 - 기본 교육과정을 중심으로 - 손지영(Son, Jiyoung); 백제순(Baek, Jehsoon); 임연화(Im, Yeonhwa) (특수교육논총, 2024)
연구목적: 본 연구는 기본 교육과정을 운영하는 특수학교에서 고교학점제 적용 시 선택과목 개설 및 운영의 다양화를 위한 지원 방안에 대해 도출하여, 특수학교에서 장애학생 맞춤형 교육과정을 구현할 수 있는 구체적인 고교학점제 지원 방안을 탐색하고자 하였다. 연구방법: 이를 위해 12명의 전문가 패널(대학교수, 교육전문직, 특수학교 교사)을 구성하여 2회에 걸쳐 델파이 조사를 실시하였다. 1차 델파이 조사를 통해 고교학점제 선택과목 개설 및 운영의 다양화를 위한 지원 방안의 기본적 틀을 구성한 다음, 2차 델파이 조사를 통해 최종안을 도출하였다. 연구결과: 특수학교에서 선택과목 개설 및 운영의 다양화 방안, 특수학교에서 다양한 선택과목 개설을 위한 특수교육 교육과정 개선 방안, 선택과목 운영을 위한 인적․ 물적 지원 방안을 도출하였다. 결론: 본 연구결과를 토대로 특수학교에서 고교학점제의 선택과목 개설 및 운영에 대한 시사점을 논의하였다. Purpose: This study aimed to derive supports to diversify the opening and operation of elective subjects when applying the high school credit system in special schools that operate the basic curriculum. Accordingly, this study explores specific measures to support the high school credit system that can implement a customized curriculum for students with disabilities in special schools. Method: A Delphi survey was conducted with a panel of 12 experts (university professors, educational professionals, and special school teachers). A basic framework was established through the first Delphi survey and the final draft was derived through the second. Results: Based on the results, plans to diversify the opening and operation of elective subjects in special schools, improve the special education curriculum to open a variety of elective subjects, and provide human and material support for the operation of elective subjects were derived. Conclusion: This study discussed implications for the establishment and operation of elective courses in the high school credit system in special schools. KCI Citation Count: 0